తెలుగు వెలుగు వాచకం 1 - Parandhama Reddy, M.; Jonnalagadda Venkateswara Sastry (My University, 1997)
This textbook has three sections: Script lessons Structural lessons and A general section containing conversations, poems, and short stories. There are four specially prepared exercises is to bridge the script lessons. The main objective of these four exercises is to bridge the script lessons with structural lessons.
Telugu Velugu I
Keywords: Telugu